Heiligung bei Paulus Ein Beitrag aus biblisch-theologischer Sicht - Stettler, Hanna (Mohr Siebeck, 2019)
Can the sanctification of Jewish and Gentile Christians be considered as the goal of Paul's mission? Hanna Stettler analyzes Paul's statements regarding sanctification against their tradition-historical background in Old Testament-Jewish literature and the Jesus tradition.